Flow cytometry evaluation of DNA integrity of alpaca sperm after cryopreservation with analogues of superoxide dismutase - Santiani A., Alexei (2012)
DNA integrity in alpaca spermatozoa was evaluated by flow cytometric analysis in sperm cryopreserved using antioxidants analogues of superoxide dismutase (Tempo and Tempol). Twelve alpaca semen samples were frozen using an extender based on skim milk, fructose, egg yolk, and ethylene glicol. Each sample was divided into three aliquots: Control group, Tempo group (1 mM), and Tempol group (1 mM). Antioxidants were added during cooling at 10 °C. After thawing, samples were fixed using 2% formaldehyde solution and permeabilizated using 0.8% Triton X-100 solution. TUNEL assay and Iodure propidium (PI) were used for evaluation of DNA integrity and cell permeability. Spermatozoa labeled with TUNEL and PI was classified as cells with DNA damaged. Samples were analyzed by flow cytometric using a 488 nm laser, counting at least 10 000 cells per sample, and by epifluorescene microscopy. Frequency of DNA damaged sperm in control group (38.8 ± 16.2%) was significantly higher (p<0.05) than in the Tempol group (16.7 ± 8.4%), whereas the results in the Tempo group (25.4 ± 5.8) were similar to the control and Tempol groups. It was concluded that the addition of superoxide dismutase analogue Tempol (1 mM) during cooling (10 °C) in alpaca sperm cryopreservation partially prevents sperm DNA damage.